Фінансовий менеджмент прибутку сільськогосподарського підприємства - Масюк, Юлія Володимирівна; Masiuk, Yuliia; Мамчур, Г. С.; Mamchur, H. (Дніпровський державний аграрно-економічний університет, 2021)
Досліджено сутність та особливості фінансового менеджменту прибутку сільськогосподарського підприємства. Доведено, що отримання прибутку є обов'язковою умовою функціонування підприємства. Прибуток розглядається як критерій ефективності відтворення і як показник, що відображає кінцевий результат інтенсивного і екстенсивного розвитку підприємства. Зокрема, сільськогосподарські підприємства працюють за принципом самофінансування і самоокупності діяльності. Зважаючи на це, отримання прибутку виступає досить важливим результативним показником їх діяльності. Досліджено основні завдання системи фінансового менеджменту прибутку сільськогосподарського підприємства Доведено, що головною метою фінансового менеджменту прибутку сільськогосподарських підприємств є забезпечення максимізації добробуту їх власників в поточному і перспективному періоді. Встановлено, що для ефективного фінансового менеджменту прибутку необхідно здійснювати удосконалення існуючих і розробку нових інструментів управління, реалізацію механізмів і стратегій управління прибутком, які відповідають сучасним економічним умовам діяльності вітчизняних підприємств. The essence and features of financial management of the profit of the agricultural enterprise are investigated. It is proved that making a profit is a prerequisite for the operation of the enterprise. Profit is considered as a criterion for the effectiveness of reproduction and as an indicator that reflects the end result of intensive and extensive development of the enterprise. In particular, agricultural enterprises operate on the principle of self-financing and self-sufficiency. In view of this, making a profit is a very important performance indicator of their activities. The main tasks of the system of financial management of profits of agricultural enterprises are proved. It is proved that the main purpose of financial management of profits of agricultural enterprises is to ensure maximization of welfare of their owners in the current and future period. It is established that for effective financial management of profit it is necessary to improve existing and develop new management tools, implement mechanisms and strategies for profit management that meet the modern economic conditions of domestic enterprises. It should be noted that being the most important indicator of the financial activity of the enterprise, profit occupies a central place in the management system of the financial system of the agricultural enterprise. In the modern economic development of the country and the formation of real independence of agricultural enterprises, profit has acquired a new meaning, because in market conditions it is not only the main source of economic activity of any enterprise, but also a stimulus to its activities. However, each company has its own problems of profit management, which require detailed consideration by the company itself. Given the above, we believe that for effective financial management of agricultural profits it is important to implement the following measures: — actively use advertising and media to raise awareness of customers about the services offered to increase new areas of demand; — to improve the skills of employees, which is accompanied by an increase in their productivity; continuously increase the level of service, ensure the completeness of services provided; — continuously analyze the state of competitors, identify their strengths and weaknesses, use experience; — reduce the level of circulation costs; this can be ensured by increasing sales of services, the implementation of internal reserves of their savings and other areas of economic activity.
Financial management of the profit of agricultural enterprise
Keywords: прибуток; profit; менеджмент; management; фінансовий менеджмент; financial management; підприємство; enterprise; управління; management; ризик; risk; фінансові ресурси; financial resources